Memory of violence and drama in Peru: the experience of the truth commission and Grupo Cultural Yuyachkani – violence and dehumanization - Lerner Febres, Salomón (International journal of transitional justice, 2020)
The theater collective Yuyachkani, a Quechua word meaning ‘I am remembering,’ were not strangers to the history the Peruvian Truth and Reconciliation Commission was rediscovering when they offered to contribute to the transitional justice process. They had been following the violence in Peru through their various performances and felt highly committed to the process of truth seeking and the search for reconciliation. The performances of Yuyachkani do not seek to reproduce the facts. They do not commit the naive error of certain realist art efforts, to portray social violence per se in a supposedly concrete way. Their tools are rather the symbols through which culture is expressed. It is not a matter so much of reproducing the facts as of producing effects, to reveal and convey the tragedies of Peruvian society. Performance heightens the senses and opens our imaginations to the deep truths that have been lost among the facts.